2015
DOI: 10.1007/s10620-015-3698-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dopamine and D2 Dopamine Receptor in the Pathogenesis of Inflammatory Bowel Disease

Abstract: Treatment with D2R agonists decreased the severity of UC in two animal models, in part, by attenuation of enhanced vascular permeability and prevention of excessive vascular leakage. Hence, the impairment dopaminergic system seems to be a feature of IBD pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 64 publications
2
48
0
Order By: Relevance
“…TER is affected by both transcellular and paracellular pathway, but alterations to the paracellular pathway have a much greater effect on TER. FITC-dextran permeability and TER have been used as common physiological indexes to evaluate gut mucosa permeability and intestinal barrier function (Wallon et al 2005, Tolstanova et al 2015. Tight junctions are the most important component for the constitutive barrier of epithelial cells, and they regulate the permeability of the barrier by tightly sealing the paracellular junctions (Oshima & Miwa 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TER is affected by both transcellular and paracellular pathway, but alterations to the paracellular pathway have a much greater effect on TER. FITC-dextran permeability and TER have been used as common physiological indexes to evaluate gut mucosa permeability and intestinal barrier function (Wallon et al 2005, Tolstanova et al 2015. Tight junctions are the most important component for the constitutive barrier of epithelial cells, and they regulate the permeability of the barrier by tightly sealing the paracellular junctions (Oshima & Miwa 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that intravenous infusion of DA or SKF-38393, an agonist of DAR-1, stimulates duodenal HCO À 3 secretion (Flemstrom et al 1993). Additionally, activation of D 2 R with quinpirole or cabergoline decreases the severity of ulcerative colitis through attenuation of vascular permeability and prevention of excessive vascular leakage (Tolstanova et al 2015). DAR are widely distributed in almost all immune cell subpopulations and serve to regulate the release of immune factors, the latter playing an important role in mucosa protection (Beck et al 2004).…”
mentioning
confidence: 99%
“…Disease activity index (DAI) was evaluated on 3 rd and 7 th days after IA enema, by summing up loss of body weight, diarrhea, lethargy as described previous ly [14]. Colon mucosa was scraped and frozen in liquid nitrogen for the further Western blot analysis.…”
Section: Animalsmentioning
confidence: 99%
“…Previously Tolstanova et al [14] showed that D2 receptor expression in the colon was altered in patients with IBD and during experimental colitis in rats. D2 receptor activation accelerated the healing of lesions during experimental colitis through the downregulation of vascular permeability and, as a result, the reduction of inflammation.…”
mentioning
confidence: 98%
“…Previously we determined changes in D2R expression in colon mucosa of patients with IBD and experimental colitis [6]. D2R activation facilitated healing of experimental colitis lesions via decreasing of endothelial permeability and, as a result, reduction of colonic inflammation [7].…”
mentioning
confidence: 99%